2015
DOI: 10.1097/rct.0000000000000168
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Reduction at Coronary Artery Calcium Scoring by Using a Low Tube Current Technique and Hybrid Iterative Reconstruction

Abstract: The radiation dose for CACS can be reduced at a low tube current and hIR without affecting the calcium score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
4
19
1
Order By: Relevance
“…This finding is in agreement with recent studies, which show smaller variability for mass scores [26,38,41,42]. Many recent studies have shown that increasing levels of iterative reconstruction causes a reduction in CCS [12,16,40,[43][44][45][46][47][48]. This result was also established in our study.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is in agreement with recent studies, which show smaller variability for mass scores [26,38,41,42]. Many recent studies have shown that increasing levels of iterative reconstruction causes a reduction in CCS [12,16,40,[43][44][45][46][47][48]. This result was also established in our study.…”
Section: Discussionsupporting
confidence: 83%
“…However, the kilovoltage was kept constant for the chest and cardiac CT for each patient and the same threshold was applied for both quantitative approaches. Lastly, we used iterative reconstructions for all reconstructions, while there are contradictory results on their influence on the absolute values of CAC scores [22][23][24][25]. This technical aspect was beyond the scope of our study and it requires further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…Several previous publications, all using multi-row single source CT, have discussed the benefits and pitfalls of different IR algorithms for noise and dose reduction in CAC evaluation. In particular, the publications on hybrid IR algorithms and model-based IR (iDose4 and IMR, Phillips Healthcare, Best, The Netherlands), as well as adaptive iterative dose reduction algorithms (AIDR 3D, Toshiba Corp. Medical Systems, Tokyo, Japan) attract attention (6,10,2224). IR algorithms allow for a significant reduction in image noise and could allow for substantial reduction in radiation dose while maintaining diagnostic accuracy as has been previously shown for other vendors than the one in the present study (22,25,26).…”
Section: Discussionmentioning
confidence: 99%